New Zealand : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes the effect of international migration on unemployment in New Zealand. The empirical results in this paper suggest that net migration inflows give rise to a fall in the unemployment rate. The paper estimates a system of equations including the unemployment rate, real wage, net migration rate, and labor force participation rate, taking into account the interdependence of the variables. It also examines the impact of exchange rate volatility on export firms' decisions to hedge foreign exchange exposure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet